The Effect Of Taxpayer Compliance On Building Earth TAX Revenue (Case Study Of Pemana Village, Sikka Regency, NTT Province) - Feni Febriani (JEKAMI Journal of Accounting, 2021)
The purpose of this study is a type of quantitative research with the aim of knowing the effect of taxpayer compliance on land and building tax receipts (Case Study of pemana Village, Sikka Regency) The type of data used in this study is quantitative data obtained from Questionnaires distributes and releads to the problem Researched Data collection was done by distributing questiooaires. The research instrument used in this study used the Likert scale scale method . The results of this study show data using statistical calculations through the Statistical Package for the Social Science (SPSS) version 24 application regerding the effect of taxpayer compliance on land and building tax revenues (Case Study of pemana Village, Sikka Regency) which has been discussed in the previous chapter, the authors draw an important conclusion, namely that taxpayer compliance has a positive and significant effect on land building tax receipts means that the higher taxpayer compliance to pay taxes, the greater the land and building tax revenue.